2019
DOI: 10.3390/agriculture9080162
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation and Selection for Cold-Tolerant Rice (Oryza sativa L.) at Germination and Seedling Stages

Abstract: Owing to its origin in tropical and subtropical areas, rice is susceptible to cold stress. Low temperatures at the germination and seedling stages can result in seed loss, a delayed transplanting period, and lower final yield. In this study, 181 rice varieties from around the world were investigated for cold tolerance at the germination and seedling stages. At the germination stage, the responses of different rice varieties were examined based on the germination index, coleoptile length, and radicle length at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…It was observed that among the 19 moderately cold-tolerant genotypes, most of the genotypes were indica types, and among the 8 very highly cold-tolerant genotypes, most of them belonged to the japonica subspecies (Table 1). This indicated that japonica rice genotypes are more tolerant of low temperatures and perform better under such conditions, similar to other studies [12,36,60]. The lowest value of CLTRI was recorded in CT6510-24-1-2 (an indica line, 6.63), whereas RU1504114 (a japonica line) showed the highest value (11.09).…”
Section: Cumulative Low and High-temperature Response Indexsupporting
confidence: 88%
See 3 more Smart Citations
“…It was observed that among the 19 moderately cold-tolerant genotypes, most of the genotypes were indica types, and among the 8 very highly cold-tolerant genotypes, most of them belonged to the japonica subspecies (Table 1). This indicated that japonica rice genotypes are more tolerant of low temperatures and perform better under such conditions, similar to other studies [12,36,60]. The lowest value of CLTRI was recorded in CT6510-24-1-2 (an indica line, 6.63), whereas RU1504114 (a japonica line) showed the highest value (11.09).…”
Section: Cumulative Low and High-temperature Response Indexsupporting
confidence: 88%
“…Attaining high yield under suboptimal growing conditions is one of the main challenges of this century. It is now clear that the emphasis on stress tolerance in plants has to be addressed from the vegetative to grain-filling stages because of their greater sensitivity to environmental variations [12,16,23]. Current constraints caused by extreme temperatures related to yield losses at the reproductive stage have gained much attention among researchers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that cold stress occurring at reproductive phase can result in a large reduction in grain yield (Thakur et al 2010;Ghadirnezhad and Fallah 2014). Additionally, slow seedling development, yellowing, withering, reduced tillering and stunted growth are always observed under cold stress at the seedling stage (Su et al 2010;Bonnecarrère et al 2011;Han et al 2017;Cong Dien and Yamakawa 2019). As a result, the cultivated area of early rice and double-season late rice is significantly reduced in China (Sun and Huang 2011;Yu et al 2012;Wang et al 2019).…”
Section: Introductionmentioning
confidence: 99%